Development of choline acetyltransferase (CAT) in the sympathetic innervation of rat sweat glands - Leblanc, G (J Neurosci, 1986)
It has been postulated that the developing sympathetic innervation of rat eccrine sweat glands changes from adrenergic to cholinergic under the influence of its target. In agreement with previous evidence that the sympathetic innervation of adult rat sweat glands is cholinergic, we found that choline acetyltransferase (CAT)-immunoreactive nerve fibers are present in adult glands, and that gland-rich chunks of adult footpads contain CAT enzyme activity. We were therefore interested in determining when CAT activity is first expressed in the developing gland innervation. Low levels of acetylating activity were observed in rat footpads as early as postnatal day 4, when sympathetic fibers first contact the glands. A greater than fourfold increase in CAT specific activity occurred between postnatal days 11 and 21. Neonatal treatment of rats with the adrenergic neurotoxin 6-hydroxydopamine (6-OHDA) eliminated most of the CAT activity in 14 and 19 d footpads. In contrast, the acetylating activity observed prior to day 11 was unaffected by neonatal 6-OHDA treatment, and only slightly reduced by the selective CAT inhibitor, naphthylvinylpyridine. These results indicate that the sympathetic fibers that innervate rat sweat glands do not acquire detectable levels of CAT activity until a full week after they contact the glands.